Keefektifan Peningkatan Kemampuan Pemecahan Masalah Matematis Siswa Kelas V melalui Aplikasi V-BAR Berbasis Android - Nur Aini, Ida; Ermawati, Diana; Hilyana, F. Shoufika (Absis: Mathematics Education Journal, 2024)
The aim of this research is to determine the effectiveness of increasing students' mathematical problem solving abilities through the use of the Android-based V-BAR (Volume Build Space) application and the PBL model in mathematics learning. The research method used is a quantitative experiment with a One one-group pretest-posttest design. The population & sample in this study were 22 class V students of SD N Sidomulyo 3. The data collected is data on problem solving abilities collected using test techniques in the form of essay questions. Data were analyzed using the N-Gain Score test statistic. The results of the research showed that there was an increase in students' mathematical problem solving abilities by 40.1% which was seen in the posttest average score of 74.6, which was better than the previous pretest average score of 34.5. Apart from that, the N-Gain Score test results showed an increase with results of 61.22% in the medium category. From the research results, it can be concluded that the use of the Android-based V-BAR application and the PBL model is effective in improving the mathematical problem solving abilities of fifth-grade students at SD N Sidomulyo 3 in the medium category.